Mapping and Complicating Conversations about Indigenous Education. Issue 2 (3rd April 2017) - Ahenakew, Cash Richard
ABSTRACT: In this article I offer a series of critical reflections about existing efforts and achievements in Indigenous Education, with particular emphasis on the risks, tensions, and paradoxes that arise where different knowledge systems meet, and when Indigenous peoples ourselves hold contradictory educational desires. I focus on the idea of the land as first teacher and on the difficulties of enabling institutional educational processes that conceptualize it as a living entity, rather than an object, a resource a property. I seek to complicate our conversations to take account of the ways that colonial interests, competing investments, and structures of schooling shape the education that Indigenous youth today receive, and how this circumscribes the kinds of education it is possible for us to imagine. I conclude by offering a cartography that enables us to map how Indigenous youth encounter different ideologies of education and schooling, I also offer some thoughts about pedagogical possibilities that emerged from a course in which students were invited by Elders to witness a Sun Dance ceremony in Turtle Island.